Level of Awareness and Challenges in Republic Act 9184 Procurement Procedures: A Basis for Training and Internal Policy Development - Dagohoy, Abigail Marie V.; Salvatierra, Armelyn C.; Constantino, Ma. Lourdes L.; Matudan, Nhorvic M.; Malang, Bernandino (Future Science / FSH-PH Publications, 2023)
ABSTRACT End-users, who act as the origin of all procurement requests, are responsible for providing technical specifications, scope of work, and terms of reference, conducting a market survey, recommending the Approved Budget for the Contract (ABC), providing technical advice, assisting in the preparation of bidding documents, and attending all stages of the procurement. This study aims to evaluate two essential aspects related to the execution of procurement activities: the level of knowledge and understanding among end-users and the difficulties they encounter while conducting procurement activities. This research used a mixed-methods approach, involving surveys and interviews, to collect data about the awareness levels and difficulties encountered by the participants regarding RA 9184 procurement procedures. In research,